BRAIN-COMPUTER MUSIC INTERFACING – CURRENT APPROACHES AND PROSPECTS (Mūzikas akadēmijas raksti, 2024)
Brain-computer music interfacing (BCMI) is a field of research addressing the idea that electrical oscillations within the brain can be used to generate or manipulate music, or support a musical activity. This is achieved by transmitting brainwave activity expressed as electrical frequencies using electroencephalogram (EEG) electrodes placed upon the scalp to a computer which maps or translates this input to audible output with musical structures or rules. The concept of using this rhythm rich EEG signal for musical applications has led to the emergence of new types of musical instruments, interactions, performances and experiences which have captured the imaginations of many artists and technologists.